2018
DOI: 10.1371/journal.pone.0197323
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution and uniformity of content of tablets developed with extract of Ximenia americana L.

Abstract: Herbal medicines currently represent an important part of the world pharmaceutical market, which shows growing interest in the use of herbal medicines. However, the production of such medicines involves a complex series of steps, which determine the production viability and the quality of the final product. Ximenia americana L. is a plant occurring in several regions of the world, with well-known and applied medicinal properties. Thus, the aim of this work was to develop and evaluate the physical and physical-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Phytochemical investigations using aqueous, ethanolic, and hydroalcoholic extracts of X. americana demonstrate the presence of condensed tannins, hydrolysable tannins, saponins, polyphenols, and flavonoids, which are responsible for various biological activities [ 13 , 14 , 15 ]. Santana et al (2018) characterized a hydroalcoholic extract of X. americana , and their results showed that it was possible to identify and quantify gallic acid as a chemical marker of X. americana .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytochemical investigations using aqueous, ethanolic, and hydroalcoholic extracts of X. americana demonstrate the presence of condensed tannins, hydrolysable tannins, saponins, polyphenols, and flavonoids, which are responsible for various biological activities [ 13 , 14 , 15 ]. Santana et al (2018) characterized a hydroalcoholic extract of X. americana , and their results showed that it was possible to identify and quantify gallic acid as a chemical marker of X. americana .…”
Section: Introductionmentioning
confidence: 99%
“…Santana et al (2018) characterized a hydroalcoholic extract of X. americana , and their results showed that it was possible to identify and quantify gallic acid as a chemical marker of X. americana . In addition, they developed X. americana tablets to combat antifungal and bacterial infections, highlighting the pharmacological potential of the species and its phytochemical components [ 14 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the determination of apparent densities, compaction, the Hausner factor, Carr index, and densification index, 100 g samples were used, which were placed in a graduated cylinder, to determine the gross volume, as described by [ 26 , 27 ]. After that, the samples were subjected to a series of 500, 750, and 1250 sequential drops, according to the properties of the powders.…”
Section: Methodsmentioning
confidence: 99%
“…In the same context, natural compounds derived from medicinal plant extracts, such as Davallina orientalis , Lepidium sativum L., Cimicifuga racemose (Actaea), Piper sarmentosum , Ormocarpum cochinchinense , Peperomia pellucida , Symphytum officinale , Chenopodium ambroisioides L., Epimedium sagittatum , Nigella sativa , Aloe vera , Sambucus williamsii , Ulmus davidiana , Spinacia oleracea , Dalbergia sissoo , Marantodes pumilum , Cassia occidentalis L. [ 15 ], Astragalus membranaceus [ 16 ], Anredera cordifolia [ 17 ], Cissus quadrangularis, Withania somnifera and Tinospora cordifolia [ 18 ], are widely used to promote bone repair. Among the most studied herbal medicines, Ximenia americana L., which is a plant that is found in various regions of the world, possesses medicinal properties that are utilized and recognized [ 19 ]. The pulverized stem of Ximenia americana L. has been recommended for the repair and control of the inflammatory process, and proven results in research carried out through experimental models showed that this extract can be used to promote tissue repair [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical investigations of Ximenia americana L. steam bark reported by Santana et al [ 19 ] and Almeida et al [ 24 ] have revealed the presence of several bioactive compounds in different extracts, including aqueous, ethanolic and hydroalcoholic extracts. These compounds include condensed tannins, hydrolysable tannins, saponins, glycosides, polyphenols, flavonoids and terpenoids [ 23 ].…”
Section: Introductionmentioning
confidence: 99%